Politicization in the Name of the Majority: The Role of Cultural, Economic, and Political Grievances - Bernd Simon; Alex Mommert; Klaus Michael Reininger (Journal of Social and Political Psychology, 2018)
The article reports two experiments that examined politicization in the name of the majority population and intergroup polarization as a function of perceived grievances of the majority population. To manipulate perceived majority grievances, we used three different injustice frames (cultural, economic, political), each of which targeted an important arena of societal participation and thus a typical breeding ground for societal injustices and psychological grievances. In addition, both experiments included a (no frame) control condition. The samples recruited for the two experiments differed from each other in (left–right) political orientation and consequently in their perceptions of and reactions to potential majority grievances. The most striking differential influences were observed for the cultural grievance symbolized by the political correctness norm. However, both experiments provided evidence that majority politicization mediates the effect of majority grievances on intergroup polarization and that, in contrast to the divisive role of majority politicization, majority solidarity likely fosters social inclusion.